2017
DOI: 10.1049/oap-cired.2017.0573
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of power quality monitoring system for the smart substation based on IEC 61850

Abstract: Along with enhancement of electrical techniques, power quality has become an important issue for both power utilities and users, leading to growing popularity of power quality monitoring systems. Previously, these systems are implemented in the traditional substations. As the smart substation based on IEC 61850 gradually becomes the major technical choice recently, the combination between smart substation and power quality is focused on by the industry. However, there is no smart substation successfully implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The authors concluded that monitoring systems with advanced measurement devices capable of providing PQ indices will rapidly increase in future power grids. Authors in Reference [141] designed a PQ monitoring system for a new generation of substations located in Shanghai, China. This system was based on international communication standards that allow remote monitoring of harmonics at a frequency of 12.8 kHz.…”
mentioning
confidence: 99%
“…The authors concluded that monitoring systems with advanced measurement devices capable of providing PQ indices will rapidly increase in future power grids. Authors in Reference [141] designed a PQ monitoring system for a new generation of substations located in Shanghai, China. This system was based on international communication standards that allow remote monitoring of harmonics at a frequency of 12.8 kHz.…”
mentioning
confidence: 99%